Neotype designation for Rhinogobius carpenteri Seale 1910, and its placement in Tukugobius Herre 1927 (Teleostei: Gobiidae) - Endruweit, Marco (Zootaxa, 2017)
In order to unravel the synonymy of Rhinogobius Gill 1859, a neotype for Rhinogobius carpenteri Seale 1910, type species of its oldest synonym, Tukugobius Herre 1927, is designated and described based on topotypic material. The genus Tukugobius is removed from the synonymy of Rhinogobius from which it is distinct in having a longitudinal cephalic lateralis system, a naked pectoral-fin base, the first dorsal fin supported by 7 pterygiophores, and the first pterygiophore of the second dorsal fin inserted in interneural space 9. Its type species further differs from other species of Philippine Tukugobius by the presence of a median naked strip along the belly.